Effects of taxes on youth self-employment and income - Johan Egebark (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2016)
This is a study of the link between taxes and youth self-employment, using a Swedish reform implemented in 2007-09 which suddenly made the payroll tax and the self-employment tax vary by age. The results suggest that youth self-employment is insensitive to tax reductions, both in the short run and in the somewhat longer run. The effect of the tax reductions on income is also studied. For those that are defined as self-employed, positive effects on income from self-employment, and negative effects on income from wage employment can be found. This finding suggests that the lower taxes caused the self-employed to reallocate time from employment to self-employment.
Keywords: H25; H32; J23; J38; J68; 330; Youth unemployment; Self-employment tax; Tax subsidy; Self-employment